STAKEHOLDER INTEGRATION IN SUSTAINABILITY-ORIENTED INNOVATION: AN APPROACH TO SUSTAINABLE BUSINESS MODEL IN SME WITHIN THE UK - Begum, Mahmuda; Islam , Mohammad Fakhrul; Mahmood , Ishtiaque; Sam-Sorungbe , Olusola (International Journal of Small and Medium Enterprises, 2025)
The sustainable business model (SBM) in the circular economy is significant to create business value and sustainability for small and medium-sized enterprises (SMEs). However, it has still received limited scholarly attention, particularly, a potential gap within the context of food and beverage SMEs in the UK. Stakeholder integration may be an essential element of SBM, playing a vital role in sustainable value creation. However, research on stakeholder integration has been fragmented and not comprehensively examined. The study examines stakeholder integration strategies in sustainability-oriented innovation (SOI) and value creation for the SBM within food and beverage SMEs in the UK. The purpose of this research is to empirically investigate how external and internal forces, and stakeholder integration, affect SOI and value creation. The study employs a qualitative case study to explore the research questions, with 30 participants from 30 food and beverage SMEs involved in sustainable practices. Data are collected through in-depth interviews, with field notes and documents. The results show that 3 contextual factors, including internal constraints, internal facilitators, and external forces, influence SOI for the SBM. The significant findings indicate that stakeholder integration not only influences SOI but also is relevant to value creation. This study developed a conceptual framework that led to a theory usable in the research context. The findings of this study suggest that practitioners and SME managers will better understand the SBM process, thereby shaping a more holistic approach to SBM. JEL Classification Codes: L26, M14, Q55.